GNSS signal propagation through ionosphere - Lee, Xian Ying (2018)
In recent years, there has been extensive use of Global Navigation Satellite System (GNSS) applications such as satellite navigation, tracking, mapping and timing. Our growing reliance on them makes it crucial for us to gain a deeper understanding on GNSS signal transmission and any jeopardizing factors that result in the degradation of signal performance. Ionospheric scintillation is a major cause of degradation of VHF/UHF signals in equatorial/low-latitude regions. Scintillation data of Singapore was obtained from Septentrio PolaRxS, a GPS receiver located at the West of Singapore at 1.34◦N, 103.68◦E. Firstly, the cause of ionospheric scintillation and the theoretical reasoning behind the well-known diurnal, seasonal and solar activity trends of amplitude scintillation in equatorial/low-latitude regions were presented. Subsequently, amplitude scintillation from September 2013 to December 2016 was analysed to confirm the well-known trends. The data was then modeled using different curve fitting methods to deduce the best empirical model and an improved Gaussian function was selected to give the best empirical model. Using the selected empirical model to ‘forecast’ the amplitude scintillation of equinox months, the forecast accuracy of the model was determined. It has been deduced that: i) Future months of October could be estimated by any past October months, ii) Future months of April could possibly be estimated by any past equinox months, iii) Future months of March could possibly be estimated by any past equinox months except October.